Therapeutic Impact of Costus (Saussurea lappa) Against Ehrlich Solid Tumor-Induced Cardiac Toxicity and DNA Damage in Female Mice - Elgharabawy, Rehab M.; El Tantawy El Sayed, Ibrahim; Abd-Allah Rezk, Nada; Tousson, Ehab (Frontiers in Pharmacology, 2021)
Breast cancer remains the most common cause of cancer deaths among women globally. Ehrlich solid tumour (EST) is a transplantable tumour model for simulating breast cancer. This study aims to describe the protective role of costus (Saussurea lappa) root against EST-induced cardiac toxicity. Forty female mice were randomly and equally divided into four groups (G1, control group; G2, costus group; G3, EST group; G4, EST+costus). The results showed that compared to the control, EST induced a significant increase in lactate dehydrogenase, creatine kinase, creatine kinase myoglobin, aspartate aminotransferase, and alkaline phosphatase activities; in potassium, chloride ion, cholesterol, triglyceride, and low density lipoprotein levels; in DNA damage and cardiac injury; and in p53 and vascular endothelial growth factor expression. Conversely, EST induced a significant decrease in sodium ion and high density lipoprotein levels and Ki67 expression compared to the control. Treatment of EST with costus improved cardiac toxicity, lipid profiles, electrolytes, and apoptosis, and protected against EST. This indicates the potential benefits of costus as an adjuvant in the prevention and treatment of cardiac toxicity.